The Beckfords in England and Italy: a case study in the musical uses of the profits of slavery. (12th June 2018) - Hunter, David
Abstract: The use of the profits of slavery to fund musical activity during the 18th century in Britain and Europe has not generated much scholarship. Although this topic may elicit surprise, disgust or indifference among some readers, the present article will dispel the notion that the topic is of minor (if any) significance. By taking the Beckford family as a case study, I show how music was an active part of the lives and patronage of several generations and branches of Jamaica's wealthiest absentee plantation and slave owners. Their chattel workforce toiled in appalling conditions to produce the sugar, molasses and rum that gave rise to the immense profits the owners spent lavishly on instruments, concerts and other performances, and, in the case of Muzio Clementi, purchasing the boy from his father in Rome. Whether it was through their friendships with the Burneys, the Mozarts, or the most notable castratos of the 1780s, or through the hiring of musicians for performances, or the purchase of top-of-the-line instruments from London makers, the Beckfords put to musical uses their slave-derived profits.